Debt Relief for Low-Income Countries : The Enhanced HIPC Initiative - Thugge, Kamau (Pamphlet Series; Pamphlet Series, ;, 1999)
This pamphlet describes the IMF-World Bank initiative begun in 1996 to address in a comprehensive manner the overall debt burden of eligible heavily indebted poor countries (HIPCs) pursuing programs of adjustment and reform supported by the two organizations. The aim of the Initiative is to reduce these countries debt to sustainable levels so that they can meet current and future debt service obligations without unduly compromising growth. This pamphlet describes the rationale for and the main features of the Initiative as it was originally conceived in 1996 and its implementation through the fall of 1999, which culminated in the approval of an enhanced HIPC Initiative in late 1999 that is aimed at providing deeper and more rapid debt relief to a larger number of countries. The enhanced HIPC Initiative also seeks to ensure that debt relief is integrated into a comprehensive poverty reduction strategy that is developed with broad-based participation and tailored to the country's circumstances.